121 INVESTIGATING THE RELATIONSHIP BETWEEN PROBABLE SARCOPENIA AND ORTHOSTATIC HYPOTENSION: FINDINGS FROM THE IRISH LONGITUDINAL STUDY ON AGEING. (25th October 2022) - Duggan, E; Murphy, CH; Knight, SP; Davis, JRC; O'Halloran, AM; Kenny, RA; Romero-Ortuno, R
Abstract: Background: Sarcopenia and Orthostatic Hypotension (OH) are emerging age-related health burdens associated with adverse outcomes including falls and functional decline. Despite a possible pathophysiological link, the association between the two disorders is not well established. We sought to further investigate this relationship in The Irish Longitudinal Study on Ageing (TILDA). Methods: Data from 2, 858 participants at wave 3 of TILDA was analysed. Probable sarcopenia was defined as per the European Working Group on Sarcopenia in Older People revised cut-offs: Hand-Grip Strength (HGS) <27kg in men, <16kg in women and/or five-chair stand test (5CST) time >15s. Participants underwent an active stand orthostatic test with non-invasive beat-to-beat blood pressure monitoring. Multivariable logistic regression models adjusting for age, sex, anthropometrics, cardiovascular diseases, medications and fear of falling were used to determine whether probable sarcopenia was a predictor of OH at multiple time-points after standing. Results: In multivariable analysis, HGS was an independent predictor of OH at 30s, 40s, 60s (P<0.01), 120s and 180s (P<0.05) but not initial OH at 10s or 20s (P=0.531, 0.464) or consensus OH (P=0.064). 5CST time was only associated with OH at 120s (P=0.030). At follow up in wave 5, four years later, those with HGS-defined probable sarcopenia had higher proportions of recurrent falls (10.5% vs 5.7%, P = 0.014), fear of falling with activity limitation (12.4% vs 6.9%, P = 0.011), hospital admission (24.2% vs 12.5%, P < 0.001) and death (4.8% vs 1.9%, P = 0.006) when compared to the non-sarcopenic group. Conclusion: Probable sarcopenia as measured by HGS, but not 5CST time is an independent predictor of orthostatic hypotension, especially in the blood pressure recovery phase 30-60s after standing. The increased rates of adverse outcomes in this group underline the importance of identification of probable sarcopenia in those at risk of OH and falls.